-10n+3(8+8n)=-6(n-4(

Simple and best practice solution for -10n+3(8+8n)=-6(n-4( equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10n+3(8+8n)=-6(n-4( equation:



-10n+3(8+8n)=-6(n-4(
We move all terms to the left:
-10n+3(8+8n)-(-6(n-4()=0
We add all the numbers together, and all the variables
-10n+3(8n+8)-(-6(n-4()=0
We multiply parentheses
-10n+24n-(-6(n-4()+24=0
We add all the numbers together, and all the variables
14n-(-6(n-4()+24=0

See similar equations:

| 8^(x-1)(x+6)=512 | | 65-3d=9-10d | | (x+1)(x^2+8x+4)=0 | | 3x(2x-1)=-21 | | |w-3|=4 | | 5x+4(1)=20 | | 10•x+45=105 | | 10=5^x | | 5^x+5^x-2=140 | | 5^x+3*5^x-2=140 | | 11x=18x+90 | | 4+3=x7 | | 3x=7-4 | | 30x=12x-40 | | 5x+0.05=3x | | 7.5x=3x-10 | | 4-2y=7y+13,y= | | 4x+7+1=-12 | | 12x=-8x+17 | | 4x=9-x^2 | | 12x=8x-17 | | 12x-10-8=10x | | 30-10b+16b+36-18b=60 | | 12x-10-4=5x | | -9x-13=-4x+3 | | x+12=52−2x | | x+5x/5-3/5=2 | | 7x-18=x-54 | | -2(f-3)=6 | | 3(r-2)=-2 | | 2•2s-10=0 | | 4x+7=10x–11 |

Equations solver categories